Possible serotonin syndrome with carbidopa–levodopa and linezolid. (February 2016) - Pettit, N. N.; Alonso, V.; Wojcik, E.; Anyanwu, E. C.; Ebara, L.; Benoit, J.‐L.
Summary: What is known and objective: Serotonin syndrome (SS) can occur when linezolid is combined with other serotonergic agents. Case description: We report a case of possible SS in an elderly patient receiving linezolid in combination with carbidopa–levodopa (CL). What is new and conclusion: Although certain classes of agents are commonly reported as causing SS among patients receiving linezolid, there are no specific case reports detailing this reaction with CL. Linezolid combined with CL should generally be avoided; however, if linezolid must be used, discontinuation of other agents with serotonergic activity is recommended with careful monitoring for signs and symptoms of SS.